Blood and violence in early modern France - Carroll, Stuart, 1965- (Oxford University Press, 2006)
The rise of civilized conduct and behaviour has long been seen as one of the major factors in the transformation from medieval to modern society. This work of archival research shows we continue to romanticize violence in the era of the swashbuckling swordsman.